Machine Vision Navigation in Spine Surgery - Kalfas, Iain H. (Frontiers in Surgery, 2021)
The advancements in computing and digital localizer technologies has led to the evolving clinical application of image-guided technology for the surgical management of spinal disorders. Image-guided spinal navigation addresses the limitations of fluoroscopy and improves the accurate placement of fixation screws. Several navigation platforms are currently available, each having its own unique advantages and disadvantages. The most recent spinal navigation system developed utilizes machine vision structured light imaging which creates a precise and detailed three-dimensional image of the exposed surface anatomy and co-registers it to a pre-operatively or intra-operatively acquired image. This system improves upon the intraoperative workflow and efficiency of the navigation process. With the continued advancements in machine vision, there is a potential for clinical applications that extend beyond surgical navigation. These applications include reducing the potential for wrong level spine surgery and providing for real-time tracking of spinal deformity correction. As the adoption and clinical experience with navigation continues to expand and evolve, the technology that enables navigation also continues to evolve.